The Effect of STAD Learning Model Using Bingo Card Media on Grade IV Students Mathematics Outcomes - Syahirah, Salsabila Rahmadina; Kasriman, Kasriman (Lectura : Jurnal Pendidikan, 2025)
This research is based on the problem of mathematics learning which is often considered difficult and boring, so it has an impact on low student learning outcomes. This study aims to see data on student learning outcomes using the Student Teams-Achievement Divisions (STAD) learning model and students who do not use the STAD learning model, and to analyze the influence of the STAD learning model based on bingo card media on the mathematics learning outcomes in grade IV of elementary school. This study used a quasi-experimental method with a pretest-posttest design. A control group of 64 students. The experimental class applied the STAD model with bingo card media, while the control class used conventional methods. Data collection was carried out through essay tests that had been tested for validity and reliability. Data analysis used normality, homogeneity, and independent tests. Sample T-test. The average post-test result of the experimental class was 87.31, higher than the control class which was 76.72. The results of the T-test showed a significance of 0.000 <0.05, which means there is a significant difference between the two classes. Therefore, the STAD learning model assisted by bingo card media is effective in improving the mathematics learning outcomes of fourth-grade students. In conclusion, STAD Learning Model using bingo card media is also able to create a more interactive, enjoyable learning atmosphere and increase students’ active involvement in learning.